2004
DOI: 10.1002/iroh.200310644
|View full text |Cite
|
Sign up to set email alerts
|

Do Protozoa Control the Elimination of Vibrio choleraein Brackish Water?

Abstract: Do Protozoa Control the Elimination of Vibrio choleraein Brackish Water?key words: Cyclidium glaucoma, ciliate feeding selectivity, toxin producing bacteria AbstractElimination of inoculated Vibrio cholerae (≥10 7 cells ml -1) within a brackish water bacteria assemblage (Mecoacán Lagoon, State of Tabasco, Mexico) was studied in laboratory microcosms with filtrationfractionated water. Feeding of a ciliate, Cyclidium glaucoma was evaluated using fluorescently labelled V. cholerae O1. Even though V. cholerae was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The long-term persistence and seasonal accumulation of V. cholerae is dependent on how it responds to this stress. Microcosm studies of natural bacterioplankton communities from the Gulf of Mexico showed that ciliates and heterotrophic nanoflagellates (HNFs) efficiently eliminate V. cholerae from environmental water samples ( Martínez Pérez et al, 2004 ). In addition, ciliates as well as flagellates can feed on V. cholerae , with grazing rates of up to 600–2,000 bacteria cell -1 h -1 ( Macek et al, 1997 ).…”
Section: Top-down Control By Predatory Micrograzersmentioning
confidence: 99%
“…The long-term persistence and seasonal accumulation of V. cholerae is dependent on how it responds to this stress. Microcosm studies of natural bacterioplankton communities from the Gulf of Mexico showed that ciliates and heterotrophic nanoflagellates (HNFs) efficiently eliminate V. cholerae from environmental water samples ( Martínez Pérez et al, 2004 ). In addition, ciliates as well as flagellates can feed on V. cholerae , with grazing rates of up to 600–2,000 bacteria cell -1 h -1 ( Macek et al, 1997 ).…”
Section: Top-down Control By Predatory Micrograzersmentioning
confidence: 99%
“…( 2016 ) showed that V. cholerae can grow inside A. castellanii. A study using laboratory microcosms of natural bacterioplankton communities from the Gulf of Mexico showed elimination of V. cholerae by ciliates and heterotrophic nanoflagellates (Martínez Pérez, Macek and Castro Galván 2004 ). In contrast, when V. cholerae biofilms were exposed to predation by flagellates, there was little effect on biofilm biomass, indicating that biofilms are protected from predation (Matz et al.…”
Section: Introductionmentioning
confidence: 99%
“…Among the microinvertebrate communities an increase in protozoan ciliates and heterotrophic nanoflagellates (HNFs) may regulate pathogenic microbial populations. Microcosm studies have shown the capacity of these microinvertebrates to eliminate V. cholerae through their grazing activities (Martı ´nez Pe ´rez et al 2004). Various ciliated protozoa can limit many bacterial populations by their predatory activities, e.g., Paramecium caudatum can rapidly ingest the Cryptosporidium oocysts (Stott et al 2001).…”
Section: Trophic Regulation and Resistance Mechanism Of Pathogenic Mi...mentioning
confidence: 99%